Ekspektasi Peningkatan Iklim Investasi Melalui Pembentukan Lembaga Pengelola Investasi - Rahayu, Kanti; Praptono, Eddhie; Rizkianto, Kus (Diktum: Jurnal Ilmu Hukum, 2022)
The high need for financing in the future has caused Indonesia's Foreign Direct Investment (FDI) level to stagnate, the ratio to GDP must remain under control, due to the increasingly limited financing capacity of SOEs. The gap between domestic funding capabilities and national infrastructure financing needs encourages governments to seek strong legal and institutional strategic partners through the establishment of Investment Management Institutions (LPI). This study aims to : 1) Describe the conditions of Indonesia's investment climate before the establishment of the Investment Management Institution (LPI); 2) Assessing expectations regarding the increase in Indonesia's investment ilkim after the establishment of the Investment Management Institution (LPI). This study uses a library research method with a normative research approach with qualitative analysis, which describes various arrangements regarding the investment climate in Indonesia before and after the existence of LPI. The finding is that the condition of Indonesia's investment climate before the establishment of the LPI was strongly influenced by the COVID-19 virus pandemic which caused our JCI to decline to below the 4000 level. The establishment of the Indonesia Investment Management Authority (LPI) or Indonesia Investment Authority (INA) is a new hope for efforts to increase investment in Indonesia. After the LPI was formed, it was followed by the formation of the Sovereign Wealth Fund (SWF). Where this SWF has also been owned by developed countries, such as the United Arab Emirates, China, Norway, Saudi Arabia, Singapore, Kuwait, and Qatar. It has been able to improve Indonesia's investment performance. It was noted that despite the Covid-19 pandemic, investment realization throughout 2020 reached IDR 826.3 trillion. This achievement is 1.1% higher than the investment target set at IDR 817.2 trillion.